2023
DOI: 10.1002/ijgo.14720
|View full text |Cite
|
Sign up to set email alerts
|

The use of the double uterine segment tourniquet in obstetric hysterectomy for bleeding control in patients with placenta accreta spectrum

Abstract: Placenta accreta spectrum (PAS) is defined as an abnormal trophoblast invasion into the myometrium, and sometimes up to or beyond the serosa. The pathogenesis is mostly due to placental implantation at an area of defective decidualization caused by pre-existing damage to the endometrial-myometrial interface. 1,2 Depending on the degree of invasion, PAS can be classified as placenta accreta when anchoring placental villi attach to the myometrium (rather than decidua), placenta increta when anchoring placental v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Some studies have also reported the benefit of using single or double uterine segment tourniquets for vascular control with highly effective results in cases of PAS. 48,49 In particular, the transverse B-Lynch suture was added to compress the lower uterine segment and reduce blood flow via the upper and lower branches of the bilateral uterine arteries. The additional uterine compression suture is the most important aspect of the MOSCUS method compared with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have also reported the benefit of using single or double uterine segment tourniquets for vascular control with highly effective results in cases of PAS. 48,49 In particular, the transverse B-Lynch suture was added to compress the lower uterine segment and reduce blood flow via the upper and lower branches of the bilateral uterine arteries. The additional uterine compression suture is the most important aspect of the MOSCUS method compared with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, besides vascular control regarding the abnormal neovascularity on the vesical surface, placental bed suture, and bilateral uterine artery ligation, a tourniquet was used in the lower part of the uterus (cervico‐isthmic segment) to achieve reduction of estimated blood loss during hemostatic procedures. Some studies have also reported the benefit of using single or double uterine segment tourniquets for vascular control with highly effective results in cases of PAS 48,49 . In particular, the transverse B‐Lynch suture was added to compress the lower uterine segment and reduce blood flow via the upper and lower branches of the bilateral uterine arteries.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the use of double uterine tourniquets, compared with non‐use, significantly reduced surgical blood loss during hysterectomy for placenta accreta spectrum (PAS) 1 . Some technical concerns arose following the publication of this paper, which we will address here.…”
Section: Figurementioning
confidence: 96%
“…Reyther et al 1 showed that the use of double uterine tourniquets, compared with non‐use, significantly reduced surgical blood loss during hysterectomy for placenta accreta spectrum (PAS).…”
Section: Figurementioning
confidence: 99%
“…
Reyther et al 1 showed that the use of double uterine tourniquets, compared with non-use, significantly reduced surgical blood loss during hysterectomy for placenta accreta spectrum (PAS).The hemostatic mechanism of a tourniquet is simple in an organ/area of one-way arterial and venous circulation (Figure 1a). The tourniquet blocks/reduces the arterial inflow, thus working toward hemostasis, whereas it blocks venous outflow, causing venous congestion, which works against hemostasis.
…”
mentioning
confidence: 99%